Understanding special educational needs : a guide for student teachers - Farrell, Michael, 1948- (London ; New York : RoutledgeFalmer, 2003)
This title is an ideal, highly accessible text for both student and newly-qualified teachers who need a reliable introduction to the vital contemporary issues within the arena of special educational needs
1. Defining and distinguishing special educational needs -- 2. Inclusion -- 3. The Special Educational Needs Code of Practice -- 4. Equal opportunities and local SEN policy -- 5. Raising educational achievement and the use of Individual Education Plans -- 6. Literacy and numeracy -- 7. Information and communications technology -- 8. Resources -- 9. Emotional, behavioural and social difficulties -- 10. Developing one's teaching -- 11. Assessment, recording and reporting -- 12. Partners and participants -- App. 1. Useful addresses -- App. 2. Internet addresses
Includes bibliographical references (pages 149-155) and indexes
Keywords: Special education teachers -- Training of -- Great Britain; Special education teachers -- In-service training -- Great Britain; Student teachers -- Great Britain; Special education -- Study and teaching -- Great Britain; Special education -- Great Britain